Key to Translation of Phaestos Disk: Genesis 49 - Cusack, Paul T. E. (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
The Philistine’s, who are thought now to be Minoans of the Island of Crete in the model of the Mediterranean Sea, were constantly at war with Israel, and are even are until this day. The Minoans have disappeared as a civilization but they left behind the Minoan Tablets (which this author has shown to be Moses’ Ten Commandments tablets received by him on Mt Sinai ) and this Phaestos Disk. It hasn’t successfully been deciphered until now. The key is Genesis chapter 49. That is where Israel (Jacob) blesses each of his sons and compares them to various animals etc. This paper shows that the disc is Hebrew in origin who of course spent 400 years in Egypt. Whoever made the disk was aware of the AT Math solution as shown by this author in previous papers.